Integrasi Latihan Decline Push-Up untuk Meningkatkan Kekuatan Fisik dan Teknik Pencak Silat dalam Program Pendidikan Jasmani - Arkanuddin, Zaenul; Nopiana, Rina; Hairurrasid, Muh. (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aimed to determine the effect of decline push-up training on arm muscle power and straight punch frequency in athletes from the PSHT Tumbuh Mulia pencak silat school in Suralaga District. The method used was an experimental pre-test and post-test design on 20 athletes, where measurements were taken before and after decline push-up training for 14 sessions. The results showed a significant effect of decline push-up training on increasing arm muscle power and straight punch frequency, with the calculated t-value greater than the t-table (18.132 > 2.093) and (13.080 > 2.093). The conclusion is that decline push-up training effectively increases arm muscle strength, which influences the quality of straight punches. Keywords: Decline Push-Up, Pencak Silat, Arm Muscle Power, Straight Punch